1997
DOI: 10.1289/ehp.97105s51291
|View full text |Cite
|
Sign up to set email alerts
|

Formation and persistence of 8-oxoguanine in rat lung cells as an important determinant for tumor formation following particle exposure.

Abstract: Exposure of rats to quartz (or various other particles) can lead to the development of lung tumors. At the moment, the mechanisms involved in particle-induced tumor formation are not clarified. However, it is suggested that inflammation, in conjunction with the production of reactive oxygen species (ROS) and an enhancement of epithelial cell proliferation, may play a key role in the development of lung tumors. ROS induces 8-oxoguanine (8-oxoGua) and other mutagenic DNA oxidation products, which can be converte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…5B). Antibody-derived TRITC signals were nearly absent in control cells but intermediate and high in the nuclei of cells exposed to 10 or 50 mM H 2 O 2 , respectively, These results confirmed earlier findings from cell culture experiments and from in vivo studies in lung tissues of rats exposed to ROS-inducing quartz particles (Nehls et al, 1997;Seiler et al, 2001). …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…5B). Antibody-derived TRITC signals were nearly absent in control cells but intermediate and high in the nuclei of cells exposed to 10 or 50 mM H 2 O 2 , respectively, These results confirmed earlier findings from cell culture experiments and from in vivo studies in lung tissues of rats exposed to ROS-inducing quartz particles (Nehls et al, 1997;Seiler et al, 2001). …”
Section: Resultssupporting
confidence: 90%
“…Slides with cells or tissue sections were incubated with rabbit anti-(8-oxoG) antibody (1 g of antibody/ml of PBS/1% BSA) for 16 h at 4°C. This antibody was characterized previously in various immunoassays (radioimmunoassay, enzyme-linked immunosorbent assay, ICA) for its specific binding to 8-oxoG and the sensitive detection of the DNA oxidation product in cultured cells and in lung tissue sections (Nehls et al, 1997;Seiler et al, 2001). After washing with PBS/BSA, adducts were visualized with goat anti-(rabbit Ig) F(ab) 2 fragments conjugated to tetramethylrhodamine B isothiocyanate (TRITC; 2 g/ml PBS/1% BSA; 45 min, 37°C; Dianova, Hamburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…A separate trials on rats administrated by inhaling and intratracheally instillating crystalline SiO 2 with respirable dimension, displayed premutagenic 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-OHdG) DNA lesions (Yamano et al, 1995;Nehls et al, 1997), occurrence of pulmonary tissue lesions (Johnston et al, 2000;Albrecht et al, 2005), and development of pulmonary carcinomas (Blanco et al, 2004). Phymatoid pulmonary damage has also been surveyed in rats' long-term post-exposure to crystalline SiO 2 at low dosages of 1 mg/m 3 (Muhle et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, neutrophils were freshly isolated from blood of one healthy nonsmoking male volunteer using gradient centrifugation (26). Lymphocytes were removed and the remaining erythrocytes were lysed using cold (4 C) lysis buffer (155 mM NH 4 Cl, 10 mM KHCO 3 , 10 mM EDTA, pH 7.4). Neutrophils were washed with PBS and finally resuspended in HBSS at 6.5 Â 10 5 cells/ml.…”
Section: Co-culture With Neutrophilsmentioning
confidence: 99%
“…In the lung, inhaled particles such as crystalline silica and those present in cigarette smoke and diesel exhaust are a potent source of inflammation, and it is suggested that pulmonary carcinogenicity upon chronic particle exposure involves an influx and subsequent activation of inflammatory phagocytes (2,3). For instance, we and others have demonstrated that in vivo DNA damage and mutagenicity upon particle exposure is closely related to neutrophil recruitment to the lung (4)(5)(6). One of the properties of phagocytes that provide a possible basis for the link between inflammation and carcinogenesis is their production of DNA damaging and mutagenic reactive oxygen species (7).…”
Section: Introductionmentioning
confidence: 99%